ИНГЛИС ҲӘМ ҚАРАҚАЛПАҚ ТИЛЛЕРИНДЕ РЕФЕРЕНСЛЕРДИ САЛЫСТЫРМАЛЫ ТАЛЛАЎ - Дәўлетмуратова, Ҳ.; Мухаммадияров, А. (FAN va JAMIYAT, 2018)
The article deals with the comparative analysis of references in English and Karakalpak languages. References are used in texts in the subject «Discourse analysis»: The authors of the article try to show the similar and different features of references in English and Karakalpak.